Tingkatkan Pengetahuan dan Perilaku Kualitas PHBS Masyarakat Pesisir di Desa Labuhan Sumbawa - Yunita Lestari; Has’ad Rahman Attamimi (Lembaga Pengembangan Kinerja Dosen, 2025)
The Clean and Healthy Living Behavior (PHBS) movement serves as a benchmark in health development efforts to improve community behavior. An individual’s health status is closely related to their behavior—the better the health-related behavior, the better the health status. This community service project aims to explore the knowledge and behavioral quality of PHBS among coastal communities in Labuan Sumbawa Village, specifically in Padak and Pasir hamlets, where all residents were the target population of the program. The implementation was carried out through a door-to-door approach, supported by undergraduate students from the Nursing and Public Health study programs. The activity was integrated with the subjects they had studied in class, namely Health Promotion, Health Education, and Community-Based Health Promotion in Coastal and Remote Areas. The expected outcomes of this community service include the application of PHBS practices in daily life, particularly in the household setting. Community members are expected to adopt handwashing practices before and after activities, especially after defecating, urinating, and before eating.